Data sharing scheme for 5G IoT based on blockchain - Kang QIAO; Wei YOU; Lingwei WANG; Hongbo TANG (网络与信息安全学报)
The massive amount of IoT data has great value,but the existing cloud-based data sharing mechanism faces problems such as single points of failure and internal leakage,which can not ensure the secure sharing of user data.In order to achieve efficient and reliable data sharing,the blockchain technology was used to propose a 5G IoT data sharing scheme based on blockchain.Firstly,the proposed scheme designed data sharing framework and data sharing process,based on the lightning network solution,an off-chain transaction mechanism for data sharing of the internet of things was proposed.Experimental analysis shows that the 5G IoT data sharing framework based on blockchain has strong anti-attack ability and the off-chain transaction mechanism based on lightning network can greatly increase transaction throughput and reduce transaction delay.